Post-9/11 veterans perceptions of the pandemic: Areas of greatest impact on health and well-being - Andrea F. Kalvesmaki; Eleanor Gonzales; Robert T. George; Huong Nguyen; Mary Jo Pugh (Elsevier, 2022)
Objective: Assess potential impacts of the COVID-19 pandemic on a subset of Post-9/11 U.S. Veterans included in a study of post-traumatic epilepsy (PTE). Methods: Two measures were added to a structured health interview for Veterans during temporary pandemic research shutdown: a validated health questionnaire [1] previously completed by survey, and a semi-structured instrument developed to assess whether pandemic conditions affected responses to the health questionnaire and identify unique impacts. Interviews were conducted between August 2020 - February 2021. Scaled items were calculated and t-tests used to compare results. Open-ended items were coded using thematic analyses. Results: Veterans identified eight major areas of impact with negative and positive impacts: mental health, family, social, work/employment, access to resources, physical health, finances, and education. Innovation: The temporary shut-down of a large health study for Post-9/11 Veterans provided an opportunity to devise an instrument to assess COVID-19's impact on health and well-being. The instrument was accepted as of the first Veteran instrument in a pandemic SDOH research repository [2], and is being used in other studies. Conclusion: This study highlights the need to assess and understand interrelated relationships of factors impacting health and well-being, especially as COVID-19 moves from pandemic to endemic with reverberating effects across multiple social determinants of health (SDOH).